Wolff-Parkinson-White syndrome with cleft lip and palate: A rare, previously unreported association - K Kannan; Rajendra Patil; Suresh Kumar (Wolters Kluwer Medknow Publications, 2008)
Wolff-Parkinson-White syndrome, also called Pre Excitation Syndrome, is characterized by an extra pathway that conducts the electrical impulses from the atria to the ventricles without the normal delay. We are reporting a case of WPW syndrome with a cleft lip and palate, which is a rare association and previously unreported in literature.